2005
DOI: 10.1162/0898929053124965
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Action-related Sentences Activates Fronto-parietal Motor Circuits

Abstract: Abstract& Observing actions made by others activates the cortical circuits responsible for the planning and execution of those same actions. This observation-execution matching system (mirror-neuron system) is thought to play an important role in the understanding of actions made by others. In an fMRI experiment, we tested whether this system also becomes active during the processing of action-related sentences. Participants listened to sentences describing actions performed with the mouth, the hand, or the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

58
640
10
16

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 950 publications
(724 citation statements)
references
References 55 publications
58
640
10
16
Order By: Relevance
“…Using abstract language as a contrasting condition for exploring motor related activity in action language is a common strategy in neuroimaging studies (Aziz-Zadeh et al, 2006;Tettamanti et al, 2005), and has also been used in a previous study of mu rhythm modulation (Moreno et al, 2013). In the latter study we also found strong evidence, based on mu suppression, that action language activates motor networks, whereas abstract language does not.…”
Section: Mu Suppression In Action Languagementioning
confidence: 59%
See 1 more Smart Citation
“…Using abstract language as a contrasting condition for exploring motor related activity in action language is a common strategy in neuroimaging studies (Aziz-Zadeh et al, 2006;Tettamanti et al, 2005), and has also been used in a previous study of mu rhythm modulation (Moreno et al, 2013). In the latter study we also found strong evidence, based on mu suppression, that action language activates motor networks, whereas abstract language does not.…”
Section: Mu Suppression In Action Languagementioning
confidence: 59%
“…Neuroimaging studies have reported activations in the motor and premotor brain regions during the comprehension of action-related language. Some of these studies found motor activation when people process action verbs presented in isolation (Hauk and Pulvermüller, 2004;Pulvermüller, 1996;Pulvermüller et al, 2005;Rizzolatti and Luppino, 2001), and others have found similar motor activation when people process action-related sentences (Aziz-Zadeh et al, 2006;Moody and Gennari, 2010;Raposo et al, 2009;Tettamanti et al, 2005;Urrutia et al, 2012;De Vega et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An MEG study showed that reading action verbs activates motor and premotor cortices both rapidly and in a somatotopic fashion (Pulvermüller, 2005), thus suggesting that motor activation is inherent to lexical processing. In a further fMRI study, listening to sentences expressing mouth, hand and foot actions produced activation of effector-congruent sectors of the premotor cortex (Tettamanti et al, 2005). Interestingly, these distinct sectors coincide, albeit only approximately, with those active during the observation of hand, mouth and foot actions (Buccino et al, 2001).…”
Section: Introductionmentioning
confidence: 84%
“…In this case, the operation of MMs is inferred when activity in a particular cortical area (as reflected in the BOLD signal) is similar during action recognition and action production, and when the cortical area is a likely homolog of an area in macaque cortex in which mirror neurons have been identified. Using this or a similar logic, it appears that the human MMs respond more to actions that the perceiver can perform than to actions the perceiver is familiar with through vision alone (Calvo-Merino et al, 2006); MMs are more sensitive to social actions than similar non-social actions (Kilner et al, 2006); MMs respond to both visually perceived actions and the linguistic description of actions (Tettamanti et al, 2005); MMs play a role in speech perception (D'Ausilio et al, 2009); activity in MMs is positively correlated with empathy (Gazzola et al, 2006) and negatively correlated with autistic behaviors (Dapretto et al, 2006). …”
Section: Introductionmentioning
confidence: 99%